Does alopecia have diagnostic weight in systemic lupus erythematosus? - Knight, Lauren Kerry (Department of Medicine, 2022)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disorder characterised by autoantibody production and a wide spectrum of clinical manifestations. Non-scarring alopecia (hair loss) is reported to occur in up to 80% of individuals with SLE, occurring primarily in the active phase. Alopecia is also reported in up to a third of the general population, begging the question of how much diagnostic weight alopecia really has in SLE. METHODS We conducted a cross-sectional cohort study of patients with confirmed SLE, by the 2012 Systemic Lupus International Collaborating Clinics (SLICC) classification criteria, managed at the Lupus clinic at Groote Schuur Hospital, a tertiary referral hospital in Cape Town, South Africa. Age, sex and race matched controls were recruited from the Dermatology clinic at the same hospital. Participants were questioned about alopecia (‘self-reported') and examined for alopecia clinically and dermoscopically (‘confirmed alopecia'). Alopecia was classified according to the likely cause and evaluated as to whether or not it was related to SLE and to disease activity. RESULTS The study included 90 participants with SLE and 90 controls. Females predominated in the study population, with a mean age of 37.13 (range 18-69) for cases and 37.62 (range 18-72) in controls. Demographics of the 2 groups were equally matched, with two thirds (64.4%) of cases and controls self- identified as being mixed race, 33.3% as black african and 2.3% as white. Alopecia (self-reported and confirmed) was found equally in cases and control groups. In a third of the people with SLE (34, 38%) alopecia was recorded by the clinician as one of the classification criteria used by the clinician in recording the diagnosis of SLE. In 7/34 (21%) of these patients, the classification of SLE would not have been made by criteria in the absence of alopecia. Forty patients were found to have clinically apparent alopecia, 7 of these (17.5%) having diffuse alopecia. Of the remaining 33 patients with alopecia, androgenic alopecia (12/33) was the commonest form. Likewise, androgenic alopecia was the commonest type of confirmed alopecia in controls (11/33, 33.3%). Patients with self-reported alopecia had significantly higher Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) scores than people without hair loss. However, there was no statistically significant difference in SLEDAI scores between those with clinically confirmed alopecia and those with self-reported alopecia (n = 40, M = 2.88, SD = 3.35 vs n = 50, M = 2.56, SD = 3.37; t = 0.44, p = 0.660, d = 0.09). CONCLUSION Within our population the incidence of alopecia was the same in people with SLE and in controls. Hair loss was identified as androgenic alopecia in the majority of affected cases and controls. This lack of difference in type of alopecia among participants highlights the low specificity of non-scarring alopecia as a criterion for SLE and further supports the weighting of classification criteria within the various domains in the EULAR/ACR criteria.